Assessment of the quality of service in the field of real estate transactions: modern methodological approaches - N. M. Kalinina; E. V. Khrapova (Омский научный вестник: Серия "Общество. История. Современность")
This article discusses topical issues related to the assessment of the quality of service in the field of real estate transactions, in particular, the theoretical and methodological approaches to determining the quantitative value of the service quality indicator. The authors summarized the existing methods for determining the estimated value of the service quality indicator, and outlined the subjective aspects of the considered methods. The author’s vision of the methodological support for establishing the estimated values of service quality indicators in the field of real estate transactions is proposed.